Effects of three storage conditions on the long-term storage and short-term reactivation performances of anammox granular sludge. (October 2021) - Wang, Xiaolong; Huang, Jialu; Gao, Dawen
Abstract: Enough anammox biomass is important for the fast start-up of anammox processes. In this study, to figure out the storage stability under three storage conditions, long-term storage treatments (up to 100 days) and following short-term re-activation treatments (<10 days) were taken for 15 biomass samples. At indoor temperatures (15.0 ± 1.6 to 21.5 ± 3.4 °C), anammox granules lost 80% of specific anammox activity (SAA) and 16% of 16S rRNA genes after 100 days. Nevertheless, anammox pathway became dominant rapidly and the SAA was re-activated to 102%. At outdoor temperatures (−20.2 ± 4.3 to −10.0 ± 5.0 °C) in the cold winter, all reactivations were failed after storage for more than 15 days, and significant declines of anammox bacterial amount and serious disintegration of anammox granules were observed. At the frozen temperature (−25 °C), SAAs were successfully recovered to at least 25.4% before 75 days of storage, and 63.2% of anammox 16S rRNA gene survived after 100 days of storage. Principal component analysis showed that recoverable SAAs were positively related to the residual SAA and negatively related to the recovery duration. Therefore, storage at room temperatures, without adding any substrates or cryoprotectants, was an economical and simple method for anammox granular biomass in practical application. Graphical abstract: Image 1 Highlights: Indoor storage of anammox sludge in water for 100 days did not cause SAA loss. Outdoor cryostorage of anammox sludge in cold Northern China was not recommended. Cryostorage of anammox sludge in a fridge for more than 75 d was not suggested. The loss of anammox bacteria and granular disintegration led to failed recovery.